Assessment of appropriate utilization of out-of-office diagnostic tools for the diagnosis of hypertension - Hussam Jnaid; Mohammed Aldosari; Mohammad Waqar Ahmad; Yaser Alendijani; Amira BaGubair; Dalal Alhaffar; Zainab Albasheer; Mansour Alrasheed (Journal of Family Medicine and Primary Care)
Background: Out-of-office blood pressure (BP) measurement devices, such as ambulatory BP monitoring (ABPM) and home BP monitoring (HBPM), enhance the accuracy and reliability of BP readings, detecting white-coat and masked hypertension. The American Heart Association (AHA) advises confirming hypertension diagnoses with ABPM to prevent overdiagnosis, emphasizing the importance of precise out-of-office diagnostic tools. This study aimed to 1) explore the prevalence of ABPM and HBPM use prior to hypertension diagnosis; 2) assess the adherence to AHA recommendations regarding ABPM utilization; and 3) investigate the association between patient characteristics and out-of-office BP monitoring practices. Methods: A retrospective cross-sectional study analyzed a random sample of adult patients newly diagnosed with essential hypertension at a tertiary hospital primary care center in Riyadh, Saudi Arabia, between 2016 and 2022. Results: This study evaluated the use of ABPM and HBPM in a sample of 268 newly diagnosed hypertensive patients, with a mean age of 49.17 ± 12.69 years. Although ABPM orders were placed for 57.8% of patients, only 48.5% completed the procedure. Notably, 42.2% of hypertension diagnoses were solely based on ABPM, while 7.1% and 1.1% utilized HBPM alone or in combination with ABPM, respectively. This analysis revealed a lower utilization of ABPM among older adults, individuals with diabetes or chronic kidney disease, and married patients (P < 0.05). However, this association with marital status, diabetes, and chronic kidney disease was no longer statistically significant in a fully adjusted model (P > 0.05). Conclusion: Out-of-office BP monitoring, particularly ABPM, was underutilized in newly diagnosed hypertensive patients, especially in older age groups and patients with specific comorbidities, who may benefit the most from this method. These results underscore the need for increasing physician knowledge and compliance with the existing guidelines.